Exposure to Perfluoroalkyl Substances and Sperm DNA Global Methylation in Arctic and European Populations. (3rd June 2014) - Leter, Giorgio; Consales, Claudia; Eleuteri, Patrizia; Uccelli, Raffaella; Specht, Ina O.; Toft, Gunnar; Moccia, Tania; Budillon, Alfredo; Jönsson, Bo A.G.; Lindh, Christian H.; Giwercman, Aleksander; Pedersen, Henning S.; et al.
<x xml:space="preserve">Abstract</x> Perfluoroalkyl substances (PFASs) are widely used in a variety of industrial processes and products, and have been detected globally in humans and wildlife. PFASs are suspected to interfere with endocrine signaling and to adversely affect human reproductive health. The aim of the present study was to investigate the associations between exposure to PFASs and sperm global methylation levels in a population of non‐occupationally exposed fertile men. Measurements of PFASs in serum from 262 partners of pregnant women from Greenland, Poland and Ukraine, were also carried out by liquid chromatography tandem mass spectrometry. Perfluorooctane sulfonate (PFOS), perfluorooctanoic acid (PFOA), perfluorohexane sulfonic acid (PFHxS), and perfluorononanoic acid (PFNA) were detected in 97% of the blood samples. Two surrogate markers were used to assess DNA global methylation levels in semen samples from the same men: (a) average DNA methylation level in repetitive DNA sequences (Alu, LINE‐1, Satα) quantified by PCR‐pyrosequencing after bisulfite conversion; (b) flow cytometric immunodetection of 5‐methyl‐cytosines. After multivariate linear regression analysis, no major consistent associations between PFASs exposure and sperm DNA global methylation endpoints could be detected. However, since weak but statistically significant associations of different PFASs with DNA hypo‐ and hyper‐methylation were found in some of the studied populations, effects of PFASs on sperm epigenetic processes cannot be completely excluded, and this issue warrants further investigation. Environ. Mol. Mutagen. 55:591–600, 2014. © 2014 Wiley Periodicals, Inc.